Culture of Corruption: Prosecutions, Persistence, and Desistence. (4th March 2022) - Artello, Kristine; Albanese, Jay S.
Abstract : Public corruption appears ubiquitous and increasing in the last few decades, according to public opinion polls. Trials and convictions of public officials usually receive extensive media attention. It is expected that high profile convictions would reduce corruption in an area as it puts individuals on notice about such behavior. Selected US Attorneys' offices appear to account for the majority of public corruption convictions. This study examines the public corruption conviction rate for all 94 US Attorneys' offices in the US. Using 52 interviews with community stakeholders, former public officials, former prosecutors, and investigators, the nature of corrupt environments is examined to find aspects of a jurisdiction that encourage or inhibit corrupt behaviors. According to interviews, local history and culture, leadership and contagion, and watchdog/oversight activity impact the culture of corruption. Leadership is a double-edged sword. Leadership can both encourage corruption and curb it. Prosecutions may serve a purpose to hold corrupt officials accountable; it does not stem the tide of corrupt cultures.